Assessment of Beach Erosion Vulnerability in the Province of Valencia, Spain - Pablo Ortiz; Isabel López; José Ignacio Pagán (Journal of Marine Science and Engineering, 2024)
This research analyses beach vulnerability to erosion along the coast of Valencia province, Spain. The Coastal Vulnerability Index (CVI) is used to assess vulnerability, considering the following variables: beach width, beach erosion/accretion rate, dune width, wave height, relative coastal flood level, submerged vegetation, upper depth limit of submerged vegetation, and percentage of vegetated dune. The results show that vulnerability varies significantly along the coast. The vulnerability assessment revealed that 26.9% of the coastal sections were classified as having very low susceptibility to erosion, 34.5% as low, 22.3% as moderate, 12% as high, and 4.3% as very high. Urbanized areas with reduced dunes are more vulnerable than natural areas with wide beaches and well-developed dunes. The study highlights and discusses limitations of the CVI method and suggests using the mean instead of the square root to calculate the overall vulnerability index due to the influence of one single variable in this formula. It is concluded that natural areas characterized by the presence of dunes exhibit a diminished vulnerability to erosion when compared to highly urbanized regions devoid of dunes and marine vegetation.